Effect of alterations of blood cholesterol levels on macrophages in the myocardium of New Zealand White rabbits - Kinscherf, Ralf; Kamencic, Huse; Deigner, Hans-Peter; Pill, Johannes; Schmiedt, Walther; Schrader, Michael; Metz, Jürgen (Journal of leukocyte biology, 1997)
We investigated the effect of alterations of blood cholesterol levels on macrophages (mphi) in the myocardium of New Zealand White (NZW) rabbits. Three groups of NZW rabbits were used: controls, rabbits fed a 0.5% cholesterol-enriched diet (CH-D) for 96 days, and rabbits fed a 0.5% CH-D for 96 days followed by normal chow for 4 months. Immunohistochemical analysis by mAbs directed against mphi (RAM-11) and Mn superoxide dismutase (MnSOD) were quantified by computer-assisted morphometry. Using cultured human and rabbit mphi, a cross-reaction of the human MnSOD mAbs was found as well as the predominant localization of MnSOD-immunoreactivity (IR) in mitochondria. In group 1, only a very few RAM-11-immunoreactive (ir) mphi occurred in the interstitial space of the myocardium. In group II blood cholesterol levels significantly increased in parallel with the numbers of mphi, which often contained lipid droplets (foam cells). Although blood cholesterol concentrations regressed about 10-fold in group III, mphi in the myocardium were found to be reduced only about 20%. Most mphi were also MnSOD-ir. In atherosclerotic coronary arteries RAM-11-IR was located in mphi and also extracellularly, whereas MnSOD-IR was found only in mphi. Drastically induced MnSOD in the mitochondria of mphi is suggested as an indicator of increased oxidative stress caused by in vitro conditions or by phagocytosis of low-density lipoprotein in vivo. Elevation of the cholesterol level leads to a long-term increase and its regression results in a delayed reduction of such mphi, which seem to play a key role in the atherogenesis of the coronary arteries as well.
Gesehen am 18.09.2017